Exergy analysis of the flow process and exergetic optimization of counterflow vortex tubes working with air. (May 2020) - Lagrandeur, Junior; Croquer, Sergio; Poncet, Sébastien; Sorin, Mikhail
Highlights: Vortex tube exergetic efficiency is higher at high cold mass fraction; Up to 51% of the exergy is consumed downstream of the vortex tube; Destruction of kinetic exergy is the main source of losses inside the tube; Higher cold outlet pressure increases the exergetic efficiency of a single tube; Efficiency of the first tube should be maximized in a cascade configuration. Graphical abstract: Abstract: Vortex tubes can separate a pressurized gas stream into a cold stream and a hot stream. However, their use is limited by the low efficiency of the device. In this article, the exergy efficiency considering transiting exergy is used to analyze the thermal exergy production and exergy destruction in vortex tubes using a thermodynamic model and experimental data from the literature. The vortex tube exergetic efficiency reaches a maximum (up to 2.88%) for a cold mass fraction around 0.7 when both the hot and the cold outlets are considered as useful. Interestingly, 45% of the available exergy is lost downstream of the vortex tube through pressure losses at this condition. Inside the vortex tube, kinetic exergy destruction represents a great portion of the irreversibilities within the tube. Furthermore, the thermodynamic model is used to maximize the efficiency of a single vortex tube. The optimization process increases the exergetic efficiency of the vortex tube to 4.4%, corresponding to an increase of 53% compared to the best experimental values. Additionally, the analysis demonstrates that increasing the cold outlet pressure increases the vortex tube exergetic efficiency for the same pressure ratio. Finally, the thermodynamic model is used to identify the vortex tubes cascade which better uses a compressed air source at 6 bars. A cold cascade with an ejector is also investigated. Results show that the cascade configuration could benefit from unused pressure from the first tube to increase the system exergetic efficiency.